Sociopolitical identity, religiosity, and motivation toward intention in Islamic banking: a behavioral reasoning theory extension - Fathoni, Muhammad Anwar; Rodoni, Ahmad; Al-Arif, Mohammad Nur Rianto; Hidayah, Nur; Mulazid, Ade Sofyan (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This research analyses the factors influencing Indonesia's largest Muslim communities' intention to utilize Islamic banking services. Method – Employing a quantitative methodology, this study targeted members of Nahdlatul Ulama (NU) and Muhammadiyah as the population. The sample consisted of 343 respondents, determined using Hair theory and selected through purposive sampling. Data was collected through a structured questionnaire and analyzed using structural equation modeling (SEM) to evaluate measurement and structural models. Findings – The findings reveal that normative beliefs significantly shape subjective norms and influence individuals' intentions to engage with Islamic banking services. Additionally, religiosity positively affects attitudes toward these services, reinforcing existing literature linking religious values to financial decision-making. Implications – Theoretically, this study implies the development of behavioral reasoning theory in Islamic finance. Practically, this study provides valuable insights into marketing strategies promoting financial inclusion among diverse religious communities.